Clinical characteristics and mortality predictors of patients with cancer hospitalized by COVID-19 in a pediatric third-level referral center - Hernández-Regino, Laura-Monserrat; De Jesús Castillejos-López, Manuel; Aquino-Gálvez, Arnoldo; Velasco-Hidalgo, Liliana; García-Guzmán, Alda; Aguilar-Ortiz, Marco; Cárdenas-Cardos, Rocío; Torres-Espíndola, Luz María (Frontiers in Pediatrics, 2022)
Background More than 135 million COVID-19 cases (coronavirus disease 2019) have been reported worldwide until today, with over 2.9 million deaths. Several studies have demonstrated that disease severity is lower in the pediatric population than in adults; however, differences are described in patients with chronic diseases, including oncological patients. Current world literature suggests patients with comorbidities, including cancer, have an increased risk of unfortunate outcomes. Therefore, our objective was to describe the clinical characteristics and epidemiological factors associated with mortality in a cohort of pediatric cancer patients hospitalized for COVID-19. Methods This is a retrospective, descriptive study of the cases of patients with cancer hospitalized for COVID-19. A total of 40 pediatrics were included in the analysis. Data from pediatric patients with COVID-19 included clinical and epidemiological records, laboratory, imaging studies, COVID-19 diagnostic methods, and medical treatment. Results Of the 40 pediatric patients admitted with cancer with a confirmed diagnosis of COVID-19, 42.5% were solid tumors, 40% leukemias, and 17.5% lymphomas. The clinical parameters associated with mortality were stage IV tumor (p = 0.029) and intubation (p < 0.001). The biochemical factors associated with lower survival were thrombocytopenia under 25,000 cells/mm3 (p < 0.001), D-dimer over 1 μg/ml (p = 0.003), clinical malnutrition (p = 0.023), and disseminated intravascular coagulation (p = 0.03). Conclusion Our findings showed that the fever was the most frequent symptom, and the clinical parameters associated with mortality were stage IV tumor, intubation, saturation percentage, RDW, platelets, creatinine, ALT, D-dimer, ferritin, and FiO2 percentage. The thrombocytopenia, D-dimer, nutritional status, and disseminated intravascular coagulation were significantly associated with lower survival.